Does financial inclusion help in alleviating poverty in United States? - Chin, Xue Yi; Lee, Shuo Zhe; Tieu, Jan Nie; Yew, Yee Mei (2023)
This FYP aims to examine whether financial inclusion helps in alleviating poverty in the United States in both long run and short run by considering the independent variables of unemployment, Gini index and domestic credit to the private sector. The tests applied in this FYP are ARDL and pairwise Granger causality test. This FYP applied secondary data by utilising 29 observations based on yearly basis from 1991 to 2019 which derived from World Bank database. The results show that all the independent variables have significant positive relationships with poverty in the United States in the long run. However, the result of domestic credit to the private sector is contrary to most of the past studies which suggested the negative relationship with poverty.